Maßnahmen und Empfehlungen für die Sicherstellung adäquater stationärer Versorgungskapazitäten für das Pandemiemanagement innerhalb einer Region – Ergebnisse eines hybriden Delphi-Verfahrens - Panchyrz, Ivonne; Hoffmann, Julia; Harst, Lorenz; Pohl, Solveig; Bauer, Michael; Blaschke, Sabine; Bodenstein, Marc; Engelhart, Steffen; Gärtner, Barbara; Graf, Jürgen; Hanses, Frank; Held, Hanns Christoph; et al. (Gesundheitswesen, 2023)
Introduction Since the beginning of the pandemic in spring 2020, inpatient healthcare has been under enormous burden, which is reflected especially in overworked staff, imprecise bed planning and/or data transfer. According to the recommendation of the Science Council, university clinics should play a controlling role in regional healthcare and act in conjunction with surrounding hospitals and practices. Methods In September 2021, 31 representatives from 18 university hospitals were invited to a hybrid Delphi study with a total of 4 survey rounds to discuss criteria for effective inpatient care in a pandemic situation, which were extracted from previous expert interviews. Criteria that were classified as very important/relevant by ≥ 75 % of the participants in the first round of the survey (consensus definition) were then further summarized in 4 different small groups. In a third Delphi round, all participants came together again to discuss the results of the small group discussions. Subsequently, these were prioritized as Optional (can), Desirable (should) or Necessary (must) recommendations. Results Of the invited clinical experts, 21 (67.7 %) participated in at least one Delphi round. In an online survey (1st Delphi round), 233 criteria were agreed upon and reduced to 84 criteria for future pandemic management in four thematic small group discussions (2nd Delphi round) and divided into the small groups as follows: Crisis Management and Crisis Plans (n = 20), Human Resources Management and Internal Communication (n = 16), Regional Integration and External Communication (n = 24) and Capacity Management and Case & Care (n = 24). In the following group discussion (3rd Delphi round), the criteria were further modified and agreed upon by the experts, so that in the end result, there were 23 essential requirements and recommendations for effective inpatient care in a pandemic situation. Conclusion The results draw attention to key demands of clinical representatives, for example, comprehensive digitization, standardization of processes and better (supra) regional networking in order to be able to guarantee needs-based care even under pandemic conditions. The present consensus recommendations can serve as guidelines for future pandemic management in the inpatient care sector.
CRIS-Team Scopus Importer:2023-09-15
Keywords: COVID-19; Delphi study; expert recommendations; inpatient pandemic management; pandemic preparedness